Systemic Lidocaine Infusions for Pediatric Patients with Cancer-Related Pain - Emily Rav; Rachna Sheth; Ali H. Ahmad (MDPI AG, 2022)
Pediatric patients with cancer experience significant distress from both treatment and cancer-related pain. Careful selection of an analgesic regimen should be based upon individual patient factors, including the level of pain, response to therapy, and physiologic profile. Refractory pain is a therapeutic dilemma frequently encountered in the pediatric cancer setting. Systemic lidocaine infusions have been described as both safe and efficacious, as prior studies show patients reporting decreased pain scores and improved quality of life after lidocaine treatment. Given the favorable side effect profile of lidocaine, it has the potential to be considered for analgesia in the setting of refractory pain. This review discusses the use of systemic lidocaine infusions for analgesia in pediatric oncology patients with cancer-related pain.